PENGARUH PENYULUHAN TERHADAP PENGETAHUAN SISWA MENGENAI PERILAKU HIDUP BERSIH DAN SEHAT DI SEKOLAH DASAR NEGERI 43 KOTA PALEMBANG - Rio Purnama (Masker Medika, 2024)
Introduction: Clean and Healthy Living Behavior (PHBS) is a group of behaviors implemented based on awareness obtained from the learning process which makes individuals or families able to help themselves in the field of health, be healthy and play an active role in achieving health. Clean and healthy community living behavior is divided into in various contexts, especially family environments, educational institutions (schools), health facilities, workplaces and public places. The aim of this research is to determine the effect of counseling on PHBS behavior among students at State Elementary School 43 in Palembang City. This type of research is analytical descriptive using the Paired Sample T-Test to determine the relationship between counseling and the level of knowledge at State Elementary School 43, Palembang City. The number of samples taken was 67 people using a total sampling technique. The results of statistical tests using the Paired T-Test obtained p=0.000 because the value was (p<0.05). This shows that there is a significant relationship between the average pre-test value (72.61) and with post test (84.55).The conclusion of this research is that there is a significant relationship between pre-test and post-test scores for students at State Elementary School 43, Palembang City. Keywords: Clean and Healthy Living Behavior (PHBS), Paired Test, school environment